Matrilineal Spirits, Descent and Territorial Power in Northern Thailand - Walker, Andrew (The Australian journal of anthropology, 2006)
This paper examines matrilineal spirits (phii puu nyaa) in northern Thailand based on field research recently undertaken in a village in Chiang Mai province. The paper suggests that the puu nyaa spirits remain locally significant—despite previous statements about their demise—and that matrilineal linkages are ideologically and practically important in the constitution of the groups. Nevertheless, there are alternative points of reference—to fathers, spouses and localities—that can attenuate attachments to matrilineal kin and introduce alternative sources of spiritual power. It becomes clear that phii puu nyaa spirit beliefs and practices are malleable and provide a basis for various orientations to spiritual power. The intermingling of different types of spiritual power is well illustrated by the presence of protective spirits locally referred to as aahak. In local perception, there is a very close relationship between phii puu nyaa and aahak, but the two entities appear to reflect quite different orientations: in simple terms the aahak represent a masculine, territorial and outward looking form of power which is contrasted with the female-focused and lineage-derived potency of the puu nyaa spirits. The paper argues that the outward orientation of the aahak provides some valuable insights into local perceptions of power, demonstrating how the supposedly peripheral and parochial draws regional power into more intimate domains.